Proposta de um modelo de apoio a processos de consultoria para a melhoria de operações de pequenas empresas - Carvalho, Leonardo Araujo de (2015)
In view of the substantial advancement in competiveness, there has been a growing interest toward debates over the potentiating mechanisms of new technologies implementations for managing the companies' operations, perceived as a organizations support ballast, and required in a globalized world, where the consumers' powerful influence has attained undeniable relevance. However, reality has shown difficulties in including these approaches in some Brazilian companies, especially in smaller ones. Incontestably, one of the barriers are the resource limitations coupled with the few low cost credit alternatives offered at the national market for this company segment. In view of this scenario, independent consultants must face the huge challenge of internalizing in these organizations models of management which are more coherent with the present economical dynamics, having as additional obstacles the natural cultural resistance against the incorporation of some recent administration philosophies, which question the traditional concepts and hold unique views, but are equally able to cause potential effective results, at low costs. This work aimed, on one hand to evaluate the context within which the small organizations are included, and on the other hand, to propose a technological model support to consultancy focused on this special business segment, in which the consultants assume preponderantly the role of educator and coach, with a view towards increasing the chances not only of implementation of updated operation management techniques, but also of its definitive incorporation in the organizations